Somatic characteristics of selected youth female players by Czech training centres - Tuma, M.; Vozobulová, P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of this research is to determine the somatotype of 41 young female handball players - members of training centers. We used Heath - Carter method (1967) to calculate somatotypes. Czech youth female players are endomorphic mesomorphs in average in all playing positions. The results are comparable with those obtained at W17 ECH in Brno 2011.